Human Research Ethics - Thamaree, Sopit (Journal of Basic and Applied Pharmacology, 2014)
Research involving human subjects contributes to knowledge, to understand the causes and effects of diseases and improve prevention, diagnosis and treatment. The safety and well-being of the individual research subject must be more important than all other interests. Investigators should comply with the local laws and regulation as well as applicable international guidelines. Regarding Belmont report, three ethical principles including, respect for person, beneficence and justice, medical research should be conducted in compliance with the ethical standards that promote respect for all human subjects and protect their health and rights. Special protection should be paid to vulnerable subjects. The research protocol must be submitted to a research ethics committee for consideration and approval before the study begins.